Validity and Reliability of Renal Dialysis Patient Dependency Classification (RDPDC) in Indonesian to Assess Dialysis Dependency in Patients Undergoing Dialysis for Chronic Kidney Disease - Setyabudhi, Verina; Rifai, Achmad; Satiti, Ika Ayu Dewi; Sagala, Ida Meita (Universitas Brawijaya, 2025)
Background: Patients with chronic kidney disease (CKD) are at risk of becoming more dependent on dialysis, which can be caused by a variety of risk factors, including physical, psychological, social, dialysis access, and medical factors. As a result, it is critical to raise awareness of this issue by using the Renal Dialysis Patient Dependency Classification (RDPDC) score tool to assess dialysis dependency in CKD patients. Aim: The purpose of this study was to determine the reliability and validity of the RDPDC scoring tool in its translated form. Methods: The RDPDC scoring tool was used to evaluate 40 CKD patients on dialysis. The assessment was carried out utilizing the Indonesian version of RDPDC. The questionnaire's reliability and validity were assessed using Cronbach's Alpha (CA) and the Pearson Validity Test. Each item's reliability was also assessed using the corrected item-total correlation. The scale is dependable if its CA value is more than 0.6 and valid if its r-value exceeds the expected r on Pearson's table. Results: The assessment tool was deemed reliable based on the CA values of both respondent groups: 0.820 for hemodialysis (HD) and 0.673 for continuous ambulatory peritoneal dialysis (CAPD). All aspects measured by RDPDC were also deemed reliable with a significance level <0.05. Pearson's validity test showed that the translated RDPDC was valid for all aspects examined, with a significance value <0.05. Conclusion: The translated RDPDC is a valid and reliable instrument for determining dialysis dependency in CKD patients undergoing regular dialysis.